Negative feedback of extracellular ADP on ATP release in goldfish hepatocytes: A theoretical study - Chara, Osvaldo (2010)
A mathematical model was built to account for the kinetic of extracellular ATP (ATPe) and extracellular ADP (ADPe) concentrations from goldfish hepatocytes exposed to hypotonicity. The model was based on previous experimental results on the time course of ATPe accumulation, ectoATPase activity, and cell viability [Pafundo et al., 2008]. The kinetic of ATPe is controlled by a lytic ATP flux, a non-lytic ATP flux, and ecto-ATPase activity, whereas ADPe kinetic is governed by a lytic ADP flux and both ecto-ATPase and ecto-ADPase activities. Non-lytic ATPe efflux was included as a diffusion equation modulated by ATPe activation (positive feedback) and ADPe inhibition (negative feedback). The model yielded physically meaningful and stable steady-state solutions, was able to fit the experimental time evolution of ATPe and simulated the concomitant kinetic of ADPe. According to the model during the first minute of hypotonicity the concentration of ATPe is mainly governed by both lytic and non-lytic ATP efflux, with almost no contribution from ecto-ATPase activity. Later on, ecto- ATPase activity becomes important in defining the time dependent decay of ATPe levels. ADPe inhibition of the non-lytic ATP efflux was strong, whereas ATPe activation was minimal. Finally, the model was able to predict the consequences of partial inhibition of ecto-ATPase activity on the ATPe kinetic, thus emulating the exposure of goldfish cells to hypotonic medium in the presence of the ATP analog AMP-PCP. The model predicts this analog to both inhibit ectoATPase activity and increase nonlytic ATP release.